Dietary dihydroquercetin alleviates age-related cognitive impairment in association with modulation of apoptosis and pyroptosis pathways - Zeng, Yongchang; Xu, Dandan; Li, Xinping; Jiang, Qianqian; Liang, Shaoyu (Frontiers in Pharmacology, 2026)
With the intensification of population aging, age-related cognitive decline has emerged as a significant global health issue. Neuroinflammation, neuronal apoptosis, and pyroptosis have been identified as key factors in neuronal loss, a hallmark of age-related neurodegenerative conditions. Dihydroquercetin (DHQ), a natural flavonoid and a new food resource, demonstrates remarkable antioxidant and anti-inflammatory properties; however, its capacity to mitigate cognitive impairment in context of apoptosis and pyroptosis remains to be fully elucidated. In this study, an ageing rat modelling by intraperitoneal injection of D-galactose was utilised to assess the therapeutic potential of DHQ. A comprehensive analytical technique, incorporating behavioural tests, TCM symptom scoring, histopathological evaluation (Hematoxylin-eosin staining and Nissl staining), ELISA, Western blotting, and molecular docking analysis, was performed to investigate its pharmacodynamic effects and potential mechanisms. DHQ supplementation significantly alleviated D-gal-induced aging phenotypes and improved learning and memory function in the Morris water maze test. Histopathological examinations indicated that DHQ mitigated neuronal damage and loss in the hippocampus whilst concomitantly increasing the number of Nissl bodies. Furthermore, DHQ administration suppressed neuroinflammation in hippocampus, as indicated by decreased levels of TNF-α, IL-1β, and IL-6. At the molecular level, DHQ treatment was associated with altered expression of proteins involved in apoptosis, specifically increasing the expression of the anti-apoptotic protein BCL2 and reducing the expression of the pro-apoptotic proteins BAX and CASP3. Crucially, DHQ supplementation significantly suppressed the activation of the TLR4/NF-κB/NLRP3/CASP1 pyroptosis-related pathway, as evidenced by decreased protein expression of TLR4, NF-κB p65, p-NF-κB p65, NLRP3, CASP1, and mature IL-1β. Molecular docking predictions suggested potential binding interactions between DHQ and key targets within both apoptotic and pyroptotic pathways. DHQ exerts a mitigating effect on age-associated cognitive impairment, possibly through its association with reduced neuroinflammation and dual modulation of neuronal apoptosis and the NLRP3 inflammasome-mediated pyroptosis pathway. This positions DHQ as a promising candidate for further investigation as a therapeutic agent or dietary supplement in ageing-related neurodegenerative conditions.